Labor Law Protection Due To Termination Of Employment Due To The Covid 19 Pandemic - Irawan Irawan; Ariman Sitompul; Melky Suhery Simamora (Universitas Dharmawangsa, 2022)
At the beginning of the Covid-19 pandemic, the implementation of policies regarding large- scale social restrictions had a very significant impact on companies in North Sumatra. Sources of data used in this study are primary and secondary data. The data analysis method used in this study is descriptive qualitative. Based on the results of the study, the conclusion in this study is the regulation of termination of employment due to the covid-19 pandemic which is regulated in Law Number 11 of 2020 concerning job creation, namely by reason of efficiency because the first in the provisions of Article 154 a paragraph of the job creation law states that